Price and Quality as Determinants of Customer Satisfaction: the Case of China Unicom - Qiao, Shichao (2016)
The study is divided into nine sections. Firstly, as many people do the first part is an overview, followed by collecting data communications sorted out the company’s development history, then the background issues. The fourth part of the article is the goal, then it is research questions and research objectives, and the last is to limit the scope. These studies can better understand the relationship between Chinese state communications, and customer satisfaction and communications companies. The ultimate goal is to identify defects and improved so that China Unicom Shanghai communications company better. Along with the facility of finding various services over internet, one of the most important and popularly rising topics of general interest nowadays is social networking websites (Robin, 2016). In this case, China United Network Communications Group Company Limited (China Unicom) on January 6, 2009 at Netcom and former China Unicom China on the basis of the original merger, in 31 provinces (autonomous regions, municipalities) and overseas countries and regions with offices, telecom companies China is the only one in New York, Hong Kong and Shanghai-listed three places at the same time, for many years appeared in the “Fortune 500 companies (He, 2010).”